Evaluation of Human Resource Governance in Improving the Efficiency of Drug Services: Study at the Outpatient Pharmacy Depot of Mokopido Regional Hospital, Tolitoli Regency, Central Sulawesi Province - Fanny Fardiyani; Rian Andriani; Yuniati Lestari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The long waiting time for medication services at the Outpatient Pharmacy Depot of Mokopido Tolitoli Regional Hospital has become a major issue in improving the quality of hospital services, as it indicates inefficiencies in the human resources (HR) management of pharmacists. This study aims to evaluate HR governance at the pharmacy depot to improve the efficiency of drug services. Identified problems include workload imbalance, patient waiting times that far exceed standards, and increasing public complaints about the lengthy service process. This study used a qualitative approach with in-depth interviews, observation, and document analysis as data collection techniques. Research participants included hospital leaders, medical support officers, pharmacy installation managers, as well as pharmacists, pharmaceutical technicians, and outpatients. The results of the study indicate that HR governance is not yet optimal. Staff needs planning is not based on workload analysis, task division is still rigid, rotation mechanisms are unstructured, competency training is limited, and the performance evaluation system is not integrated with quantitative indicators such as prescription service waiting times. These conditions indicate a gap between managerial policies and operational needs in the field. Based on these findings, improving HR governance is a strategic step to increase service efficiency. The practical implications of this research emphasize the importance of workload-based HR planning, task flexibility and rotation, and the development of measurable training and performance evaluation to support continuous improvement.